Characterization of a polyubiquitin gene in T. thermophila and of ubiquitin gene expression during sexual reproduction and under stress conditions - Guerreiro, Paulo (2014)
A 5-unit polyubiquitin gene, TTU3, was isolated from a T. thermophila genomic library and sequenced. This gene presents an extra triplet coding for Phe, a AGAGA motif and a putative HSE element in its 5'-non-coding region. The ubiquitin gene expression in this ciliate was investigated by Northern blot hybridization in conjugating cells or cells under stress conditions. Exponentially growing cells express two ubiquitin mRNAs of 0.75 and 1.8 kb and a new species of 1.4 kb is induced under hyperthermic stress. During sexual reproduction of the cells (conjugation) the 1.8-kb mRNA is still transcribed whereas the steady-state population of the 0.75 mRNA transcripts is strongly diminished. Southern blot analysis suggests that ubiquitin in T. thermophila constitutes a large family of about ten members.